RELEVANCE OF LANGUAGE, THOUGHT AND CULTURE: SYSTEMATIC LITERATURE REVIEW - Marina Pakaja, (International Journal of Innovations in Engineering Research and Technology, 2023)
Understanding the complex relationship between language thought and culture involves how language is used to express thoughts and influence a person's way of thinking and how culture affects the language and thoughts of an individual or group. The method used is Systematical Literature as a comprehensive and rigorous approach to reviewing the literature on the relationship of language, thought and culture according to the hypothesis of Edward Sapir, Benjamin Lee Whorf, Lev Vygotsky, Clifford Geertz, and Noam Chomsky. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) process, with the rules of identification, screening, and eligibility included, assists researchers in presenting various systematic reviews and meta analyses per the subject matter. Linguistic relativity suggests that humans have different communication competence because they have different ways of thinking. This different meaning is due to a person's language expressing the meaning or meaning of the world around them differently based on their cultural identity. The hypotheses of Edward Sapir, Benjamin Lee Whorf, Lev Vygotsky, Clifford Geertz, and Noam Chomsky are theoretically derived from the basic principles of linguistic relativity. Their hypothesis could be that the structure of a person's commonly used language can influence how people think and behave. Differences in cultural identity and human thought stem from differences in a person's language and cognitive acquisition.